Functional impairment in South African children with Obsessive-Compulsive disorder and Attention-Deficit/Hyperactive Disorder - Fischer, Mareli (Department of Psychology, 2014)
The electromagnetic pulse (EMP) resulting from the detonation of nuclear explosives is a documented and studied phenomenon. What is less well known and understood is the simi- lar yet considerably less powerful occurrence surrounding the detonation of high explosives. The phenomenon was rst noticed by Kolsky in 1954 during his investigation into stress waves using explosive charges. This project was undertaken to identify any discernible eld or wave in the low frequency EM spectrum, focusing particularly on the magnetic eld. The work published by Soloviev in 2002 and Adushkin in 2004 served as guidelines on test procedure and setup. Testing of this nature was not found in the literature to have been previously conducted in South Africa and is multi-disciplinary, involving the elds of detonics and signal processing. The test procedure implemented proved valid as signals were detected and su cient data were gathered to perform basic pattern recognition and spectral frequency analysis. The analysis allowed for comments to be made on the relationship between the signal and other characteristics surrounding the event. Inside the frequency band investigated there appeared to be two bands of activity in the kHz range, which is consistent with previously published works. The repeatability of the waveforms shape for identical blasts was good but with the limited sample size a proper database could not be developed. Provisionally it can be said that such events do have characteristic shapes. Testing revolved around small charges and was conducted in the near eld. This removed the possibility of commenting on orientation factors. The testing was a success in terms of recording magnetic eld signals from the detonation of high explosives.